China Land Policy Reform for Sustainable Economic and Social Development : An Integrated Framework for Action - World Bank (Washington, DC, 2012)
China has undergone a profound economic and social transformation as it moves from a centrally-planned to a market-oriented economy. Land issues are implicated in this ongoing transformation in numerous important ways - as key factors in China's quest for economic growth, national food security and social stability; as important influences in the rapid growth of China's cities as well as the future of its agriculture; and as central features in local government finance and in the growth and stability of the financial and banking sector. It is clear that decisions concerning land - how it is allocated, how it is used, how it is governed, how it is administered and how it is financed - will play a central role in determining the shape and trajectory of China's economic and social future. The purpose of this report is to present in a synthesised fashion the main lessons that have emerged so far from the World Bank collaboration, and on that basis to suggest concrete proposals for moving forward, in the short, medium and long term. In addition, land policy reforms have sought to put in place mechanisms, incentives and sanctions that will stimulate more rational allocation of land between competing land uses. Receiving particular attention from the central government in this respect has been the problem of accelerating conversion of agricultural land to urban uses.